Sedimentary architecture of the microbial mound–shoal complex: a case study of the Ediacaran Dengying Formation, Sichuan Basin, China - Xia, Qinyu; Guo, Zhenhua; Zhang, Fei; Zhang, Lin; Xu, Rui; Wang, Xue; Li, Wenzheng; Shi, Shuyuan; Yan, Haijun; Liu, Yuyang (Frontiers in Earth Science, 2025)
The Ediacaran Dengying Formation in the Sichuan Basin exhibits well-developed microbial mound–shoal complex (MMSC) sedimentation. Its abundant outcrops, core samples, and thin section data provide advantageous conditions for sedimentary architecture studies. Based on these data, this study elucidates typical lithofacies, identifies sedimentary architectural elements, summarizes MMSC stacking styles, describes sedimentary evolution characteristics, and explores the controlling factors of different stacking styles and the reservoir development conditions of architectural elements. Research indicates that MMSC primarily develops five lithofacies, namely, thrombolitic dolomite, undulate stromatolitic dolomite, laminar stromatolitic dolomite, granular dolomite, and micritic dolomite. MMSC sedimentary architecture is categorized into composite MMSCs, single MMSCs, and lithofacies. Three stacking styles of MMSCs are observed, namely, superimposed MMSCs, which represent aggradational sedimentation; migratory MMSCs, which depict progradational sedimentation; and isolated MMSCs, which denote a single parasequence depositional cycle. The stacking styles of MMSCs are fundamentally controlled by the relationship between MMSC sedimentation rates and variations in accommodation space, with the latter predominantly influenced by fluctuations in sea level. Superimposed MMSC sedimentation rates are comparable to accommodation space change rates, while migratory MMSC sedimentation rates exceed accommodation space change rates, and isolated MMSC sedimentation rates are lower than accommodation space change rates. Various composite MMSCs are isolated from each other by sediments formed under low hydrodynamic conditions, constituting distinct connectivity units. Compared to isolated MMSCs, superimposed and migratory MMSCs exhibit superior reservoir conditions. Within individual MMSCs, different lithofacies lead to high-quality reservoirs in mound cores and flanks due to variations in physical properties, while mound bases, flats, and caps form non-reservoirs.